Discovery of polarized X-ray emission from the accreting millisecond pulsar SRGA J144459.2–604207 - Papitto, Alessandro; Di Marco, Alessandro; Poutanen, Juri; Salmi, Tuomo; Illiano, Giulia; La Monaca, Fabio; Ambrosino, Filippo; Bobrikova, Anna; Cristina Baglio, Maria; Ballocco, Caterina; Burderi, Luciano; Campana, Sergio; et al. (EDP Sciences, 2025)
We report the discovery of polarized X-ray emission from an accreting millisecond pulsar. During a 10-day-long coverage of the February 2024 outburst of SRGA J144459.2-604207, the Imaging X-ray Polarimetry Explorer (IXPE) detected an average polarization degree of the 2-8 keV emission of 2.3%+/- 0.4% at an angle of 59 degrees +/- 6 degrees (east of north; the uncertainties quoted are at the 1 sigma confidence level). The polarized signal shows a significant energy dependence with a degree of 4.0%+/- 0.5% between 3 and 6 keV and < 1.5% (90% c.l.) in the 2-3 keV range. We used NICER, XMM-Newton, and NuSTAR observations to obtain an accurate pulse-timing solution and to perform a phase-resolved polarimetric analysis of IXPE data. We did not detect any significant variability in the Stokes parameters Q and U with the spin and orbital phases. We used the relativistic rotating-vector model to show that a moderately fan-beam emission from two point-like spots at low magnetic obliquity (similar or equal to 10 degrees) is compatible with the observed pulse profile and polarization properties. IXPE also detected 52 type I X-ray bursts whose recurrence time Delta t(rec) increased from 2 to 8 h as a function of the observed count rate C as Delta t(rec) proportional to C-0.8. We stacked the emission observed during all the bursts and obtained an upper limit on the polarization degree of 8.5% (90% c.l.).